Uji Fitokimia Metabolit Sekunder Daun Ubi Jalar Ungu (Ipomoea batatas (L.) Lamk) - Ade Irawan; Teguh Adiyas Putra; Citra Tasya Ulwia (BORNEO JOURNAL OF PHARMASCIENTECH, 2022)
Purple sweet potato leaf is a plant that is widely consumed by the community as a vegetable and traditional medicine for various diseases. This study aims to determine the components of secondary metabolites contained in purple sweet potato leaves with laboratory experimental methods. Purple sweet potato leaves were extracted by immersion in water using 70% ethanol (1:5) for 24 hours, then evaporated with a rotary evaporator under vacuum to form a concentrated extract. In addition, phytochemical screening tests were carried out with the results of purple sweet potato leaf extract containing alkaloids (+), flavonoids (+), tannins (+), saponins (+), terpenoids (+), steroids (-), triterpenoids (+). Meanwhile, the TLC test found that Rf 0.9 blue irradiated with UV 364 was suspected to be a flavonoid compound.